Model and Approach in Evaluation of English Language Learning: Irene, Yohanisa - Irene (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2023)
This study aims to describe theoretically the learning evaluation model and approach. The method used in this study is the literature review method. This method emphasizes textbooks as sources and studies. The results of this study found that the learning evaluation model is divided into two namely: a quantitative evaluation model and a qualitative evaluation model. Quantitative evaluation models include the black box Tyler model, theoretical model, CIPP model, and Alkin model. In contrast, the qualitative evaluation model includes a case study model, an illuminative model, and a responsive model. Learning evaluation approaches include traditional approaches and systems approaches. By applying this evaluation model and approach to learning, the learning evaluation process in the classroom will be systematic and the resulting output will be in line with the expectations of the education system